2008
DOI: 10.2174/187152108785908811
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies as Anti-Infective Agents in Medicinal Chemistry

Abstract: The treatment of infectious diseases has been complicated by the rising of new pathogens, the spread of antibiotic-resistant strains and the relative inefficacy of antimicrobial chemotherapy in immunocompromised hosts. This has led to renewed interest in the utilization of antibody-based therapies as anti-infective agents. Antibody-based therapies are effective against a wide variety of pathogens. In recent years they have become first-line therapy for a variety of conditions that include viral infections, inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Affinity detection and purification of human immunoglobulin G (IgG) are commercially important because of the highly specific nature of IgG. Monoclonal and polyclonal antibodies are the most highly consumed protein biotherapeutic molecules 26,27 and they play vital roles in applications such as immunoaffinity chromatographic separation, 28 immunoassays, and immunosensors. 29 Conventional purification and detection of IgG is based on proteinaceous ligands such as Staphylococcus aureus Protein A and Streptococcus Protein G. However, the high costs, low stability, and loss of antibody activity due to harsh elution conditions associated with these proteinaceous ligands have been a major motivation for designing less expensive and more robust synthetic, small ligands.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Affinity detection and purification of human immunoglobulin G (IgG) are commercially important because of the highly specific nature of IgG. Monoclonal and polyclonal antibodies are the most highly consumed protein biotherapeutic molecules 26,27 and they play vital roles in applications such as immunoaffinity chromatographic separation, 28 immunoassays, and immunosensors. 29 Conventional purification and detection of IgG is based on proteinaceous ligands such as Staphylococcus aureus Protein A and Streptococcus Protein G. However, the high costs, low stability, and loss of antibody activity due to harsh elution conditions associated with these proteinaceous ligands have been a major motivation for designing less expensive and more robust synthetic, small ligands.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Affinity detection and purification of human immunoglobulin G (IgG) are commercially important because of the highly specific nature of IgG. Monoclonal and polyclonal antibodies are the most highly consumed protein biotherapeutic molecules , and they play vital roles in applications such as immunoaffinity chromatographic separation, immunoassays, and immunosensors . Conventional purification and detection of IgG is based on proteinaceous ligands such as Staphylococcus aureus Protein A and Streptococcus Protein G. However, the high costs, low stability, and loss of antibody activity due to harsh elution conditions associated with these proteinaceous ligands have been a major motivation for designing less expensive and more robust synthetic, small ligands. The use of specific peptide ligands for biosensing functional proteins may offer a promising alternative to protein-based biomolecules for use as the biorecognition interface of biosensors. , By screening a one-bead-one-peptide combinatorial library, a hexamer peptide ligand, HWRGWV, was identified that exhibits high affinity and specificity to the Fc fragment of human IgG. , Chromatographic resins bearing the peptide were able to purify human IgG from various complex mixtures including two different commercial Chinese hamster ovary (CHO) cell culture media with purities and recoveries higher than 85% and 94%. ,, Remarkably, it was possible for the resins bearing the peptide ligand to be eluted in milder conditions than those of protein A.…”
Section: Introductionmentioning
confidence: 99%